Reading the Text of Judges 19:1-30 from the Perspective of Grace: Ji-Sun Kim’s Theology of Intersectionality - Randan, Sindy (Feminist theology, 2025)
Intersectionality theology recognizes the complex interplay between various social identities and power structures, such as gender, social status, economic status, and sexuality, and their influence on individual lived experiences. The use of intersectionality theology by the researcher, Grace Ji-Sun Kim, is because this theology provides a new perspective that theology can start from the experiences of the marginalized and discriminated against by a person’s multiple and intersecting identities as a lens in theology. By applying this framework to the text of Judges 19:1-30, this study seeks to account for the marginalized and oppressed concubine in this narrative and examine how her identities intersect in shaping her experience. The analysis begins by engaging with the historical and socio-cultural context to understand the social dynamics at play. By considering a theological perspective on intersectionality, this study seeks to challenge traditional interpretations that ignore or minimize the experiences of marginalized individuals in biblical narratives. This research aims to encourage a more inclusive approach to reading and understanding biblical texts by revisiting the text of violence against the nameless concubine and making it a warning against future violence against individuals with marginalized identities.